Firm Efficiency of East Asia Countries: The Impact of Board Busyness. Issue 2 (June 2019) - Tan, Khar Mang; Kamarudin, Fakarudin; Noordin, Bany-Ariffin Amin; Rahim, Norhuda Abdul
This study aims to examine the impact of board busyness on firm efficiency under the concept of technical efficiency. By employing conventional agency theory and busyness hypothesis, the logical relationships between board busyness and firm efficiency are established. In the first stage of analysis, this study employs data envelopment analysis (DEA) to investigate firm efficiency. While in the second stage of analysis, this study adopts panel regression analysis to empirically examine the proposed effect of board busyness on firm efficiency, based on a sample of 400 listed firms in the countries of significant East Asia region from 2009 to 2015. This study discovers the significant and negative impact of board busyness on firm efficiency, suggesting that the busy board significantly impedes firm efficiency due to their overcommitted issue and therefore consistent with busyness hypothesis and agency theory. This study highlights practical implication for managers who pursue to enhance firm efficiency in attaining the goals of profit maximization by understanding how board busyness impacts the firm efficiency. In addition, this study calls for regulators and government policymakers to review the restrictions on board busyness in preventing the overcommitted issue of busy boards.